Uncertain empire : American history and the idea of the Cold War - Isaac, Joel, 1978-; Bell, Duncan, 1976- (Oxford ; New York : Oxford University Press, 2012)
Historians have long understood that the notion of ""the cold war"" is richly metaphorical, if not paradoxical. The conflict between the United States and the Soviet Union was a war that fell ambiguously short of war, an armed truce that produced considerable bloodshed. Yet scholars in the rapidly expanding field of Cold War studies have seldom paused to consider the conceptual and chronological foundations of the idea of the Cold War itself. In Uncertain Empire, a group of leading scholars takes up the challenge of making sense of the idea of the Cold War and its application to the writing of.
Cold War degree zero / Anders Stephanson -- Exploring the histories of the Cold War : a pluralist approach / Odd Arne Westad -- A history best served cold / Philip Mirowski -- Inventing other realities : what the Cold War means for literary studies / Steven Belletto -- The geopolitical vision : the myth of an outmatched U.S.A. / John Thompson -- War envy and amnesia : American Cold War rewrites of Russia's war / Ann Douglas -- The spirit of democracy : religious liberty and American anti-communism during the Cold War / Andrew Preston -- God, the bomb, and the Cold War : the religious and ethical debate over nuclear weapons, 1945-1960 / Paul S. Boyer -- Blues under siege : Ralph Ellison, Albert Murray, and the idea of America / Daniel Matlin -- Cold War culture and the lingering myth of Sacco and Vanzetti / Moshik Temkin -- Deconstructing "Cold War anthropology" / Peter Mandler -- Cognitive and perceptual training in the Cold War man-machine system / Sharon Ghamari.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Politics and culture -- United States -- History -- 20th century; Cold War -- Social aspects -- United States; Cold War -- Historiography; World politics -- 1945-1989.; United States -- Intellectual life -- 20th century; United States -- Foreign relations -- Soviet Union; Soviet Union -- Foreign relations -- United States; Politique et culture -- États-Unis -- Histoire -- 20e siècle.; Guerre froide -- Aspect social -- États-Unis.; Guerre froide -- Historiographie; Politique mondiale -- 1945-1989.; États-Unis -- Vie intellectuelle -- 20e siècle.; États-Unis -- Relations extérieures -- URSS; URSS -- Relations extérieures -- États-Unis.; HISTORY -- United States -- 20th Century; Diplomatic relations; Historiography; Intellectual life; Politics and culture; Social aspects; World politics; Soviet Union; United States; 1900-1999; History